PEMBINAAN ORGANISASI KEBUDAYAAN DI KABUPATEN SUMEDANG OLEH DISPARBUDPORA - Nugraha, Dadan Setia; Rohidin, Amin; Mubarokah, Dela Riska; Khairani, Lystia; Irawan, Reval; Putri, Rindu Syahrani Iklima; Melinda, Wida Nur (JRPA - Journal of Regional Public Administration, 2025)
The aim of the research conducted by the researchers was to analyze how cultural organizations in Sumedang Regency are fostered by Disparbudpora, what factors hinder it, and how to overcome the obstacles. The research method used in this research is a qualitative research method. With research informants, namely the Head of Culture, Functional Position in the Cultural Sector, Regional Arts and Culture Expert Staff. The data collection techniques used were literature study and field study consisting of observation, interviews and documentation. Meanwhile, the processing procedures in this research are data reduction, data presentation, data verification and triangulation. Based on the research results, it was concluded that the development of cultural organizations carried out by the Sumedang Disparbudpora showed that the Cultural Organization at the Sumedang Regency Tourism, Culture, Youth and Sports Department was effective. This was reviewed from the preparation of guidance guidelines carried out by Disparbudpora and then by determining the methods carried out directly into the field. The inhibiting factor in developing cultural organizations is the budget factor, which currently the government, especially the government departments, is still trying to maximize the development of cultural organizations. Disparbudpora's efforts to overcome factors inhibiting the development of organizational groups include efforts to increase training and development as well as improving facilities and infrastructure.